2018
DOI: 10.1109/lsens.2018.2848542
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Bragg Grating in CYTOP POF at 600-nm Wavelength

Abstract: published 5 xx 201x, current version xx xxx 201x. (Dates will be inserted by IEEE; "published" is the date the accepted preprint is posted on IEEE Xplore ® ; "current version" is the date the typeset version is posted on Xplore ®).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Since then, great progress has been made in the POFBG fabrication. Different materials such as TOPAS [9][10][11], ZEONEX [12,13], CYTOP [14][15] or even polycarbonate [16][17] were introduced for different sensing modalities with unique advantages. However, until now, PMMA remains the preferred material for POFs composition.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, great progress has been made in the POFBG fabrication. Different materials such as TOPAS [9][10][11], ZEONEX [12,13], CYTOP [14][15] or even polycarbonate [16][17] were introduced for different sensing modalities with unique advantages. However, until now, PMMA remains the preferred material for POFs composition.…”
Section: Introductionmentioning
confidence: 99%
“…Marques et al [104] reported the inscription of gratings in POFs made of different materials (TOPAS, ZEONEX, and Polycarbonate) under 248 nm wavelength, and compared it with the same fiber irradiation under 325 nm, resulting in a reduction of the irradiation time by at least 16 times (Table 2) and better stability when 248 nm wavelength is employed. Min et al [58] obtained the first 600 nm wavelength grating with commercial CYTOP POF, using a 248 nm KrF laser system with a repetition of 40 Hz and average pulse energy of ~0.60 mJ during ~60 min, as shown in Figure 4, with potential applications in the visible range.…”
Section: Different Polymer Materialsmentioning
confidence: 99%
“…A Moiré structure is formed by superimposing two gratings of equal amplitude but with slightly different periods. Figure 6a shows the result of two superimposed pulses on a singlemode, BDK-doped mPOF by using a 248 nm KrF laser emitting an output pulse power of 2.5 mJ Min et al [58] obtained the first 600 nm wavelength grating with commercial CYTOP POF, using a 248 nm KrF laser system with a repetition of 40 Hz and average pulse energy of~0.60 mJ during~60 min, as shown in Figure 4, with potential applications in the visible range. Min et al [58] obtained the first 600 nm wavelength grating with commercial CYTOP POF, using a 248 nm KrF laser system with a repetition of 40 Hz and average pulse energy of ~0.60 mJ during ~60 min, as shown in Figure 4, with potential applications in the visible range.…”
Section: Special Grating Devicesmentioning
confidence: 99%
See 2 more Smart Citations